PENGARUH PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DAN PARTISIPASI MASYARAKAT TERHADAP PENYELENGGARAAN PENDIDIKAN - Rahmayani, Dinda; Arafat, Yasir; Mulyadi, Mulyadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
This study describes the influence of the principal's leadership behavior and community participation on the implementation of education at SMP Negeri 11 Prabumulih. The method used is descriptive analytical survey method. Data collection techniques and procedures through, questionnaires, observation and documentation. Data were analyzed using multiple linear regression. Based on the data analysis, the conclusion are 1) There is an influence of the principal's leadership behavior on the implementation of education at SMP Negeri 11 Prabumulih City. 2) There is an influence of community participation on the implementation of education in SMP Negeri 11 Prabumulih City. 3) There is an influence between leadership behavior and community participation together on the implementation of education at SMP Negeri 11 Prabumulih City. Principal leadership behavior and community participation are able to influence the implementation of education with a contribution of 24.2%, while the remaining 75.8% is influenced by factors not included in this study.